2014
DOI: 10.1038/cgt.2014.59
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vav3 could reverse the drug resistance of gastric cancer cells by downregulating JNK signaling pathway

Abstract: This study aims to investigate the effect and mechanism of Vav3 on the multidrug resistance of gastric cancer. Fluorescence quantitative RT-PCR and western blot assay were used to detect Vav3 and drug resistance genes in gastric cancer tissues as well as gastric cell lines such as SGC7901, SGC7901/adriamycin (ADR) and GES-1. Besides, Vav3-specific small interfering RNA (Vav3-siRNA) was applied to inhibit Vav3 in SGC7901/ADR, and SRB assay was used to determine chemosensitivity. After that, drug resistance gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Therefore, we speculate that LXR623 kills tumour cells by promoting cholesterol efflux and inhibiting cholesterol influx. We also found other upregulated or downregulated genes related to cell proliferation, invasion and metastasis, such as VAV3, CDH17, MMP1 and MMP13 33,34 . It can be speculated that LXR agonists and inverse agonists act on tumour cells in different ways, causing decreases in intracellular FA and cholesterol contents to inhibit tumour cells ( Fig.…”
Section: Sr9243 and Lxr623 Kill Ccrcc Cells Through Different Mechanismsmentioning
confidence: 60%
“…Therefore, we speculate that LXR623 kills tumour cells by promoting cholesterol efflux and inhibiting cholesterol influx. We also found other upregulated or downregulated genes related to cell proliferation, invasion and metastasis, such as VAV3, CDH17, MMP1 and MMP13 33,34 . It can be speculated that LXR agonists and inverse agonists act on tumour cells in different ways, causing decreases in intracellular FA and cholesterol contents to inhibit tumour cells ( Fig.…”
Section: Sr9243 and Lxr623 Kill Ccrcc Cells Through Different Mechanismsmentioning
confidence: 60%
“…Moreover, the overexpression of multidrug resistance proteins by tumor cells causes efflux of various chemotherapeutic drugs. [5][6][7] Therefore, new chemotherapeutic agents are sorely needed.…”
Section: Introductionmentioning
confidence: 99%
“…47 In addition, siRNA-based downregulation of Vav3 yields a significant decrease in MDR1/P-gp, GST-p, Bcl-2 and Bax expression in gastric cancer cells. 50 In conclusion, we herein demonstrate for the first time that truncated Vav3.1 and not full-length isoform of Vav3, is clinically relevant in the pathophysiology of ovarian cancer. Importantly, Vav3.1 also appears to be decisively involved in mechanisms causing intrinsic drug resistance.…”
Section: Increased Vav31 Expression In Platinum-refractory Patientsmentioning
confidence: 51%
“…Recent data showed that knock‐down of Vav3 sensitizes paclitaxel (PTX)‐resistant cancer cells to PTX treatment . In addition, siRNA‐based downregulation of Vav3 yields a significant decrease in MDR1/P‐gp, GST‐π, Bcl‐2 and Bax expression in gastric cancer cells …”
Section: Discussionmentioning
confidence: 99%